Association Between Time–Averaged Serum Uric Acid Level and Subsequent Renal Involvement in Premenopausal Patients with Systemic Lupus Erythematosus - Choi, Su Jin; So, Min Wook; Yoo, Kyung Don; Lee, Sunggun; Choi, Seung Won; Lim, Doo-Ho (Archives of Rheumatology, 2025)
Background/Aims: Serum uric acid (SUA) is a potential risk factor for renal involvement in systemic lupus erythematosus (SLE). However, the impact of cumulative SUA levels on subsequent renal involvement in premenopausal women remains unclear. The association between cumulative SUA levels and the development of subsequent renal involvement in premenopausal patients with SLE was evaluated. Materials and Methods: A retrospective review of 112 premenopausal women with newly diagnosed SLE, and no renal involvement at diagnosis was conducted in a tertiary medical center. Clinical characteristics at diagnosis and during follow-up were compared between patients who developed subsequent renal involvement and those who did not. Timeaveraged SUA (TA-SUA) was calculated from the area under the curve during follow-up. Cox proportional hazards analysis was performed to evaluate the factors associated with subsequent renal involvement. Results: The median TA-SUA level among 112 patients was 4.2 mg/dL (IQR, 3.8-4.8). During a median follow-up of 4.4 years, 25 patients developed subsequent renal involvement. The proportion of patients with TA-SUA level ≥4.2 mg/dL was higher in patients with subsequent renal involvement than in those without (84.0% vs. 46.0%, P = .001). In multivariate Cox analysis, TA-SUA level ≥4.2 mg/dL was associated with a higher risk of subsequent renal involvement (hazard ratio 6.389, P = .014). Systemic lupus erythematosus disease activity index score and the presence of anti-Smith antibodies at diagnosis were also associated with subsequent renal involvement. Conclusion: High TA-SUA levels are independently associated with an increased risk of subsequent renal involvement in premenopausal patients with SLE, underscoring the importance of cumulative SUA levels. Cite this article as: Choi SJ, So MW, Yoo KD, Lee SG, Choi SW, Lim DH. Association between time-averaged serum uric acid level and subsequent renal involvement in premenopausal patients with systemic lupus erythematosus. Arch Rheumatol. 2025;40(4):427-434.